Polyoxime urethane as well as preparation method and application thereof

By controlling the sequence of dynamic covalent units, adjusting the oxime urethane group distribution of dynamic polymers, the contradiction between self-healing properties and mechanical properties of dynamic polymers is solved, and the mechanical strength and self-healing properties of the polymer are realized. promote.

CN119192527APending Publication Date: 2024-12-27SHENZHEN CHILDRENS HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292979.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There is a contradiction between the self-healing performance and mechanical properties of dynamic polymers, and existing design strategies are not enough to effectively regulate their performance.

Method used

By controlling the sequence of dynamic covalent units, polyoximide urethane is synthesized by one-step and two-step methods to adjust the distribution of oxime urethane groups, thereby regulating the mechanical strength and self-healing properties of dynamic polymers.

Benefits of technology

The mechanical strength improvement and self-healing performance of dynamic polymers have been achieved. SCP-1 has faster self-healing speed, and the maximum tensile strength is almost twice that of SCP-2. The rheological characteristics and degradation characteristics also show obvious sequences. Dependency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192527A_ABST
    Figure CN119192527A_ABST
Patent Text Reader

Abstract

The invention relates to a poly (oxime urethane) and a preparation method and application thereof, in a molecular chain of the poly (oxime urethane) controlled by a sequence synthesized by a one-step method, oxime urethane groups are distributed relatively uniformly, and in a molecular chain of the poly (oxime urethane) controlled by a sequence synthesized by a two-step method, the oxime urethane groups are distributed relatively intensively. The related performance of the dynamic polymer can be effectively regulated and controlled through sequence control of the oxime urethane group, and a foundation is laid for wide popularization of the dynamic polymer in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and particularly relates to polyoxime urethane and a preparation method and application thereof. Background Art

[0002] Polymer materials have become one of the most important materials today due to their remarkable structural diversity and adjustable properties. Data show that the annual global production of synthetic polymers is currently estimated to be about 35-40 billion tons, and it is predicted that this figure will soar to more than 60 billion tons by 2035. However, with the widespread production and application of polymer materials, the related polymer waste has increased rapidly, causing a series of serious resource and environmental problems, including the negative impact on the ecosystem and human and animal health that cannot be ignored.

[0003] To solve this urgent problem, researchers introduced dynamic bond strategies into polymer materials, including both non-covalent bonds and dynamic covalent bonds, and developed a series of dynamic polymers with breakthrough properties. These materials not only break the boundaries between traditional thermoplastic and thermosetting polymers, but also exhibit unique properties such as self-healing, providing a new solution for the development of sustainable polymers. However, the development of dynamic polymers still faces many challenges, one of the most pressing issues being the contradiction between the self-healing properties and mechanical properties of polymers.

[0004] In recent years, with the continuous development of the field of dynamic chemistry, the field of dynamic polymers has also become increasingly prosperous. However, it is obviously not enough to design dynamic polymers based solely on a limited number of dynamic chemical species. The latest design strategies cover multiple aspects such as integrating multiple dynamic bonds and regulating network topology, providing a more flexible approach to developing dynamic polymers with unique properties. In these designs, polymer molecular chains play a key role as components of topological networks. However, it is worth noting that research on sequence-controlled dynamic polymers is relatively limited. Summary of the invention

[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a polyoxime urethane and a preparation method and application thereof.

[0006] The present invention provides a polyoxime urethane, the structural formula of the polyoxime urethane is:

[0007]

[0008] Wherein m=any integer between 1 and 30; n=any integer between 1 and 30; x=any integer between 1 and 30;

[0009] The R is a portion of diisocyanate without two isocyanate groups.

[0010] The present invention provides a method for preparing polyoxime urethane, comprising method 1 or method 2,

[0011] Method 1: Mix diol, oxime, diisocyanate and solvent, stir and dissolve under protective gas at room temperature, add catalyst, stir, then heat and dry to obtain polyoxime urethane;

[0012] The method 2 comprises mixing a diol, a diisocyanate and a solvent, stirring and dissolving them under protective gas conditions at room temperature, adding a catalyst, stirring, and then adding an oxime and a diisocyanate, stirring, heating, and drying to obtain a polyoxime urethane.

[0013] Preferably, the diol in method 1 and method 2 is polytetramethylene glycol with a molecular weight of 500-5000 gmol -1 ; The oxime is dimethylglyoxime; the diisocyanate is isophorone diisocyanate; the solvent is anhydrous tetrahydrofuran; the catalyst is dibutyltin dilaurate; and the protective gas is nitrogen.

[0014] In the method 1 and the method 2, the molar ratio of diol, oxime and diisocyanate is 1-3:2-4:4-6, the amount of catalyst is 0.001-1% of the total mass of the reactants, and the amount of solvent is 0.1-50 times the total mass of the diol.

[0015] Further preferably, in the method 1 and the method 2, the molar ratio of diol, oxime and diisocyanate is 2:3:5-5.5.

[0016] Preferably, in the method 1, mixing the diol, oxime, diisocyanate and solvent specifically comprises: adding the diol, oxime, diisocyanate and solvent in sequence and mixing;

[0017] Preferably, in the method 2, mixing the diol, diisocyanate and solvent comprises: adding the diol, diisocyanate and solvent in sequence and mixing them.

[0018] Preferably, in method 1, diol, oxime, diisocyanate and solvent are mixed, stirred and dissolved under protective gas conditions at room temperature, a catalyst is added, and the temperature is raised to 60° C. and stirred for 1-3 hours, then gradually raised to 90° C. within 12 hours, and dried to obtain polyoxime urethane.

[0019] Further, the catalyst is added and stirred as described in method 1, and then the reactants are poured into a mold in an oven, and the temperature is gradually increased from 70° C. to 90° C. within 12 hours. The mold is a polytetrafluoroethylene mold.

[0020] Preferably, in method 2, the diol, the first part of the diisocyanate, and the solvent are mixed, stirred and dissolved under protective gas conditions at room temperature, a catalyst is added, stirred at 60° C. for 0.5-2 h, and then the oxime and the remaining diisocyanate are added, stirred for 1-2 h, and then gradually heated to 90° C. within 12 h, and dried to obtain polyoxime urethane.

[0021] Furthermore, in method 2, oxime and diisocyanate are added, stirred, and the reactants are poured into a mold in an oven, and the temperature is gradually increased from 70° C. to 90° C. within 12 hours. The mold is a polytetrafluoroethylene mold.

[0022] Preferably, the first portion of diisocyanate accounts for 1 / 4 to 1 / 2 of the total amount of diisocyanate.

[0023] The drying in method 1 and method 2 is performed at 40° C. for 24-48 hours.

[0024] The invention provides application of the polyoxime urethane in tire and shoemaking industries.

[0025] Beneficial Effects

[0026] The present invention proposes a novel strategy to simultaneously enhance the mechanical strength and self-healing properties of dynamic polymers by controlling the sequence of dynamic covalent units. The present invention successfully prepared polyoxime urethane with different sequences of oxime urethane groups by simply controlling the feeding order of chemicals. In the molecular chain of the sequence-controlled polyoxime urethane (SCP-1) synthesized by a one-step method, the oxime urethane groups are distributed relatively evenly, while in the molecular chain of the sequence-controlled polyoxime urethane (SCP-2) synthesized by a two-step method, the oxime urethane groups are distributed relatively concentratedly. Although the two sequence-controlled polymers have been adjusted to have similar molecular weights, the differences in the sequence structures of their molecular chains significantly affect the properties of the resulting polymers. SCP-1 not only exhibits a faster self-healing speed than SCP-2, but also has a maximum tensile strength that is almost twice that of SCP-2. In addition, the rheological properties and degradation properties of SCP-1 and SCP-2 also show obvious sequence dependence. These research results show that the relevant properties of dynamic polymers can be effectively regulated by sequence control of oxime urethane groups, laying a foundation for their wide promotion in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the reaction equation of sequence-controlled polyoxime urethane 1 (SCP-1);

[0028] Figure 2 The reaction equation for sequence-controlled polyoxime urethane 2 (SCP-2) is:

[0029] Figure 3Design of two sequence-controlled polyoxime urethanes; (a) Schematic diagram of the molecular structure of SCP-1 prepared by a one-step reaction; (b) Schematic diagram of the molecular structure of SCP-2 prepared by a two-step reaction;

[0030] Figure 4 ATR-FTIR spectra of SCP-1 and SCP-2;

[0031] Figure 5 For SCP-1 and SCP-2 1 HNMR spectrum;

[0032] Figure 6 are the GPC curves of SCP-1 and SCP-2;

[0033] Figure 7 The schematic diagram is a diagram showing that the amine groups act as scissors to cut the molecular chains of SCP-1 and SCP-2 at the oxime urethane groups, and the schematic diagram of the molecular structure of the oxime urethane groups being aminolyzed by n-pentylamine;

[0034] Figure 8 GPC curves of SCP-1-amine and SCP-2-amine;

[0035] Fig. 9 The loss modulus of (a) SCP-1 and (b) SCP-2 obtained by DMA test varies with temperature;

[0036] Fig.10 are the DSC curves of SCP-1 and SCP-2;

[0037] Fig.11 Variation of G′ and G″ with frequency for (a) SCP-1 and (b) SCP-2;

[0038] Fig.12 is the variation of complex viscosity of SCP-1 and SCP-2 with frequency;

[0039] Fig.13 is the variation of complex viscosity of SCP-1 and SCP-2 with temperature;

[0040] Fig.14 Normalized stress relaxation curves of (a) SCP-1 and (b) SCP-2 at different temperatures; (c) point distribution diagram of Ln(τ) and 1000 / T, and the fitting line according to the Arrhenius equation, τ is the characteristic relaxation time;

[0041] Fig.15 The degradation of SCP-1 and SCP-2 in deionized water at 80°C;

[0042] Fig.16(a) Tensile stress-strain curves of SCP-1 and (b) SCP-2; (c) Photograph of SCP-1 under tension;

[0043] Fig.17 (a) Cyclic tensile stress-strain curves of SCP-1 and SCP-2; (b) Damping capacity of SCP-1 and SCP-2 calculated from the cyclic tensile stress-strain curves;

[0044] Fig.18 (a) Tensile stress-strain curves of the original and self-repaired SCP-1, the inset is an enlarged view of the tensile stress-strain curve within 10 times the strain; (b) Tensile stress-strain curves of the original and self-repaired SCP-2, the inset is an enlarged view of the tensile stress-strain curve within 10 times the strain;

[0045] Fig.19 Microscopic images of scratch self-healing of SCP-1 and SCP-2 at ambient temperature. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0047] Related tests and characterizations involved in the embodiments:

[0048] Fourier Transform Infrared Spectroscopy:

[0049] The Fourier transform infrared (FTIR) spectra of the samples were obtained on a Nicolet 8700 spectrometer equipped with an attenuated total reflectance (ATR) test accessory. The test was carried out in the attenuated total reflectance mode with a data collection range of 500–4000 cm -1 , number of collections: 32.

[0050] H NMR spectrum:

[0051] The H NMR spectrum of the sample ( 1 H NMR) was obtained on a nuclear magnetic resonance spectrometer (AVANCE III 600 MHz) using deuterated dimethyl sulfoxide as solvent, with an acquisition number of 32.

[0052] Gel Permeation Chromatography:

[0053] The gel permeation chromatography (GPC) test of the samples was obtained on a gel permeation chromatograph (GPC-50) using N,N-dimethylacetamide as the eluent and polystyrene was used for curve calibration.

[0054] For the aminolysis test, 3.5 mg of the sample was dissolved in a solution of N,N-dimethylacetamide containing 20 μL of n-pentylamine and allowed to stand for 12 hours. The resulting solution was used for GPC test.

[0055] Differential Scanning Calorimetry

[0056] The differential scanning calorimetry (DSC) analysis of the samples was carried out on a differential scanning calorimeter (Q20) in a nitrogen atmosphere using an aluminum crucible at a heating rate of 10 °C min. -1 For SCP-1 and SCP-2 samples, the temperature program was set to increase from 25°C to 120°C, then decrease to -70°C, and then increase to 120°C. For TPOU and CPOU samples, the temperature program was set to increase from 25°C to 160°C, then decrease to -70°C, and then increase to 160°C. Data analysis was based on the data from the second temperature increase.

[0057] Dynamic Thermomechanical Analysis:

[0058] The dynamic mechanical analysis (DMA) test of the sample was carried out on a dynamic mechanical analyzer (DMA1) using a rectangular sample with a strain of 0.1%, a frequency of 1 Hz, and a temperature change rate of 5 °C min -1 For SCP-1 and SCP-2 samples, the temperature program was set to increase from -60°C to 40°C. For TPOU and CPOU samples, the temperature program was set to increase from -100°C to 100°C.

[0059] Thermogravimetric analysis:

[0060] Thermogravimetric analysis (TGA) of the samples was carried out on a thermogravimetric analyzer (TG 209F1) at 20 °C min-1 in a nitrogen atmosphere. -1 The temperature change rate is from 30℃ to 600℃.

[0061] Rheological testing

[0062] Rheological tests of the samples were carried out on an advanced rotational rheometer (ARES-G2) using 8 mm parallel plate fixtures and round pancake-shaped samples.

[0063] For SCP-1 and SCP-2 samples: temperature sweep, strain 1%, frequency 1Hz, temperature range 25℃ to 100℃; frequency sweep, strain 1%, temperature 25℃, frequency range 10 -2 Hz to 10 2Hz; variable temperature stress relaxation, using strain control mode, strain is 5%, the test was carried out at temperatures of 25℃, 30℃, 35℃, and 40℃ respectively.

[0064] For TPOU and CPOU samples: temperature scanning, strain of 0.5%, frequency of 1Hz, temperature range of 25℃ to 160℃; variable temperature stress relaxation, using strain control mode, strain of 1%, tested at temperatures of 70℃, 80℃, 90℃, 100℃, 120℃, 125℃, 135℃, and 140℃ respectively.

[0065] Calculation of network apparent activation energy:

[0066] The initial stress relaxation modulus (G0) is normalized to the stress relaxation modulus (G), and according to the exponential decay function G(t) = G0exp(-t / τ*), the characteristic relaxation time (τ*) is taken as the time when G0 / G reaches 0.37. a ) is calculated according to the following Arrhenius equation: lnτ*(T)=lnτ0+E a / RT, where τ0 is the characteristic relaxation time at infinite temperature, R is the universal gas constant, and T is the absolute temperature.

[0067] Mechanical properties test:

[0068] The mechanical properties of the samples were tested using an electronic universal materials testing machine (Exceed E42) equipped with a 100N sensor.

[0069] For SCP-1 and SCP-2 samples: cuboid samples were used and the deformation rate for a single tensile test was 50 mm min -1 The deformation rate of the cyclic tensile test is 10 mm min -1 .

[0070] Self-healing performance test:

[0071] The scratch self-healing test was performed by scratching the sample film with a razor blade, and the change of the scratch width trajectory was observed using an optical microscope (MDA2000).

[0072] The self-healing test of mechanical properties is to cut the sample into two pieces and manually splice the cross-sections and repair them under different conditions, and then conduct mechanical tests. The self-healing efficiency is defined as the ratio of the maximum tensile strength after repair to the maximum tensile strength of the original sample.

[0073] Degradation test

[0074] The samples were immersed in deionized water at 80 °C, washed with deionized water every 24 hours, dried in a vacuum oven and weighed. At least three specimens were tested for each sample and the average value was taken.

[0075] Polytetramethylene glycol (1000 g mol -1 ) and isophorone diisocyanate (99%) were from Shanghai Aladdin Biochemical Technology Co., Ltd., and dimethylglyoxime (98%) was from Sinopharm Chemical Reagent Co., Ltd.

[0076] Example 1

[0077] Sequence-controlled synthesis of polyoxime urethane 1:

[0078] Polytetramethylene glycol (molecular weight 1000 g mol -1 , 8.00g, 8.00mmol), dimethylglyoxime (1.39g, 12.00mmol), isophorone diisocyanate (4.54g, 20.40mmol) and anhydrous tetrahydrofuran (20mL) were added to an eggplant-shaped reaction bottle in sequence and dissolved with magnetic stirring under a nitrogen atmosphere at room temperature. Dibutyltin dilaurate (0.05g) was added, and the system temperature was raised to 60°C and stirred for 2.5 hours. Subsequently, the reactants were poured into a polytetrafluoroethylene mold in an oven, and the temperature was gradually increased from 70°C to 90°C within 12 hours. Finally, sequence-controlled polyoxime urethane 1 (SCP-1) was obtained after vacuum drying at 40°C for 48 hours. The reaction equation is as follows Figure 1 shown.

[0079] Example 2

[0080] Sequence-controlled synthesis of polyoxime urethane 2:

[0081] Polytetramethylene glycol (molecular weight 1000 g mol -1 , 8.00g, 8.00mmol), isophorone diisocyanate (2.27g, 10.20mmol) and anhydrous tetrahydrofuran (20mL) were added to an eggplant-shaped reaction bottle in sequence and dissolved under a nitrogen atmosphere at room temperature with magnetic stirring. Dibutyltin dilaurate (0.05g) was added, and the system temperature was raised to 60°C and stirred for 1.1 hours. Then, dimethylglyoxime (1.39g, 12.00mmol) and isophorone diisocyanate (2.27g, 10.20mmol) were added to the reaction system and further stirred for 1.4 hours. Subsequently, the reactants were poured into a polytetrafluoroethylene mold in an oven, and the temperature was gradually increased from 70°C to 90°C within 12 hours. Finally, sequence-controlled polyoxime urethane 2 (SCP-2) was obtained after vacuum drying at 40°C for 48 hours. The reaction equation is as follows Figure 2 shown.

[0082] result:

[0083] Design and synthesis of sequence-controlled polyoxime urethanes:

[0084] Sequence-controlled polyoxime urethane was easily synthesized by using commercially available polytetramethylene glycol, dimethylglyoxime and isophorone diisocyanate under the catalysis of dibutyltin dilaurate. SCP-1 was successfully synthesized by a one-step reaction using the above-mentioned raw materials ( Figure 3 a). SCP-2 is synthesized using a two-step reaction ( Figure 3 b): First, polytetramethylene glycol is reacted with isophorone diisocyanate to form a prepolymer, and then reacted with dimethylglyoxime and isophorone diisocyanate added subsequently.

[0085] In the molecular chain of SCP-1, the oxime urethane groups are relatively dispersed, and compared with SCP-2, the content of long non-dynamic chain segments generated by the reaction of polytetramethylene ether diol and isophorone diisocyanate is less. In the molecular chain of SCP-2, the oxime urethane groups are relatively concentrated, and the content of long non-dynamic chain segments formed is higher.

[0086] Structural Characterization of Sequence-Controlled Polyoxime Urethanes:

[0087] The structures of SCP-1 and SCP-2 were first confirmed by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. Figure 4 As shown, the peaks at 3406 cm-1, 3315 cm-1 and 1719 cm-1 correspond to free NH groups, hydrogen-bonded NH groups and C=O groups, respectively, indicating the successful formation of urethane groups. The peak at 985 cm-1 corresponds to the NO group. No peak corresponding to the N=C=O group is shown near 2260 cm-1, indicating that the isophorone diisocyanate monomer has been completely reacted and converted.

[0088] H NMR ( 1 H NMR) was further used to characterize the structures of SCP-1 and SCP-2. SCP-1 and SCP-2 have similar 1 The HNMR spectrum shows that they have similar molecular structures. The attribution of hydrogen protons in the spectrum is as follows: Figure 5 In addition, the signals corresponding to tetrahydrofuran at 1.85 ppm and 3.76 ppm are basically negligible, indicating that the solvent tetrahydrofuran has been completely removed.

[0089] According to the GPC results ( Figure 6), the weight average molecular weight (Mw) of SCP-1 and SCP-2 were calculated to be 31.9 kDa and 29.2 kDa, and the polydispersity index (PDI) was 1.29 and 1.27, respectively. These results confirmed the successful synthesis of SCP-1 and SCP-2.

[0090] Subsequently, the sequence structures of SCP-1 and SCP-2 were characterized. The oxime urethane group can be aminolyzed, so the amine group can cut the molecular chain of SCP-1 and SCP-2 like a pair of scissors, leaving a non-dynamic chain segment generated by the reaction of polytetramethylene glycol and isophorone diisocyanate ( Figure 7 ).

[0091] The two sequence-controlled polymers SCP-1 and SCP-2 were reacted with n-pentylamine, and the reaction mixtures (referred to as SCP-1-amine and SCP-2-amine) were subsequently analyzed by GPC. After the reaction with n-pentylamine, the molecular weights of SCP-1-amine (17.1 kDa) and SCP-2-amine (16.0 kDa) decreased ( Figure 8 ). As expected, the peak of SCP-1 in the high molecular weight range is higher than that of SCP-2, indicating that SCP-1 contains more long non-dynamic fragments than SCP-2. These results prove that SCP-1 and SCP-2 have different molecular chain sequence structures.

[0092] Basic properties of sequence-controlled polyoxime urethane:

[0093] SCP-1 and SCP-2 were systematically characterized and compared to evaluate the effect of sequence structure on material properties.

[0094] First, the thermomechanical behaviors of SCP-1 and SCP-2 were investigated by dynamic thermomechanical analysis (DMA). Fig. 9 As shown, the loss modulus of SCP-1 and SCP-2 decreases as the temperature increases. The glass transition temperature (Tg) takes the maximum value of the loss modulus, and the Tg of SCP-1 and SCP-2 are -55℃ and -53℃ respectively.

[0095] The thermal properties of SCP-1 and SCP-2 were studied by differential scanning calorimetry (DSC). Fig.10 As shown, SCP-1 and SCP-2 do not show crystallization or melting transition in the DSC curves from -50°C to 100°C, indicating that SCP-1 and SCP-2 are in an amorphous state at ambient temperature.

[0096] Sequence control of rheological properties of polyoxime urethane:

[0097] The two sequence-controlled polymers, SCP-1 and SCP-2, were further characterized by rheological tests. The storage modulus (G′) and loss modulus (G″) of SCP-1 and SCP-2 showed obvious frequency dependence ( Fig.11 ), a phenomenon that can often be found in dynamic polymer materials. The intersection of G′ and G″ indicates the transition point between the liquid and solid states of the material. The frequency of the transition point of SCP-1 is 2.2Hz, which is lower than the transition point frequency of SCP-2, which is 6.8Hz, indicating that SCP-1 can exhibit more solid properties than SCP-2 at lower frequencies.

[0098] The complex viscosity of SCP-1 and SCP-2 also has obvious frequency dependence, decreasing with increasing frequency ( Fig.12 ). Within the tested frequency range, the complex viscosity of SCP-1 is always greater than or close to that of SCP-2, indicating that the interaction force between the polymer molecular chains of SCP-1 is greater than that of SCP-2.

[0099] In addition, the complex viscosity of SCP-1 and SCP-2 also showed obvious temperature dependence, decreasing with increasing temperature ( Fig.13 ). Similar to the frequency dependence of complex viscosity, the complex viscosity of SCP-1 is always greater than that of SCP-2 within the tested temperature range, further indicating that the intermolecular forces of polymers in SCP-1 are greater than those in SCP-2.

[0100] The dynamic behavior of the polymer networks of SCP-1 and SCP-2 was further characterized by a series of stress relaxation experiments at different temperatures. Fig.14 As shown, both polymers exhibit rapid network reconstruction capabilities, where increasing temperature is more conducive to rapid network relaxation. The characteristic relaxation times of SCP-1 and SCP-2 follow the Arrhenius equation, and their network apparent activation energies (Ea) are calculated to be 34.78 kJmol-1 and 41.72 kJmol-1, respectively. The network apparent activation energy of SCP-1 is lower than that of SCP-2, indicating that SCP-1 has a stronger network rearrangement ability than SCP-2. This shows that sequence structure plays an important role in the rearrangement of dynamic polymer molecular networks. Network rearrangement also plays an important role in the self-healing properties of polymers.

[0101] Sequence Control of Degradation Properties of Polyoxime Urethane

[0102] The degradation properties of sequence-controlled polyoxime urethane were studied. Fig.15As shown in Figure 2, both SCP-1 and SCP-2 showed significant degradation in deionized water at 80 °C, which may be mainly caused by the hydrolysis of oxime urethane groups. In the first 4 days, the degradation rates of SCP-1 and SCP-2 were similar. After 5 days, the degradation rate of SCP-2 was greater than that of SCP-1, which may be due to the fact that the relatively concentrated oxime urethane groups in SCP-2 are more conducive to hydrolysis than the dispersed oxime urethane groups.

[0103] Sequence Control of Mechanical Properties of Polyoxime Urethane

[0104] The mechanical properties of sequence-controlled polyoxime urethanes were evaluated. Fig.16 As shown, the tensile strength of SCP-1 (0.45±0.04MPa) is almost twice that of SCP-2 (0.25±0.02MPa). At the same time, the maximum elongation of SCP-1 (more than 100 times) is also much higher than that of SCP-2 (67±11 times).

[0105] In order to study the energy dissipation capacity of sequence-controlled polyoxime urethane, SCP-1 and SCP-2 were subjected to repeated cyclic tensile tests at a constant strain (20%), and their damping capacity was calculated. The damping capacity is defined as the ratio of the dissipated energy (hysteresis loop area) to the load energy (area under the load stress-strain curve). Fig.17 As shown, the damping capacity of SCP-1 is higher than that of SCP-2 in all stretching cycles, indicating that SCP-1 has better energy dissipation ability than SCP-2.

[0106] Sequence-controlled self-healing properties of polyoxime urethane:

[0107] In order to characterize the mechanical self-healing properties of sequence-controlled polyurethane, the strips of SCP-1 and SCP-2 were completely cut, and then their cross sections were spliced ​​together and allowed to heal at ambient temperature for 30 minutes. Fig.18 As shown in the figure, the tensile stress-strain curves of the repaired SCP-1 and SCP-2 are almost the same as those of the original materials, which may be due to the dynamic reorganization of hydrogen bonds and oxime urethane bonds in the polyurethane network. In addition, after self-repair under the same conditions, although the repair efficiency of SCP-1 and SCP-2 is close to 100%, the mechanical properties of SCP-1 after healing are better than those of SCP-2, which can also explain to some extent that the self-repair ability of SCP-1 is stronger than that of SCP-2.

[0108] The self-healing ability of SCP-1 and SCP-2 was then evaluated by a scratch recovery test. The SCP-1 and SCP-2 films were scratched with a razor blade, and the changes in the scratches were recorded using an optical microscope at room temperature. Fig.19As shown in the figure, the artificial scratches on the surface of SCP-1 and SCP-2 films almost completely disappeared within 30 seconds and 120 seconds, respectively, indicating that these two sequence-controlled polyoxime urethanes have excellent spontaneous self-healing ability. The self-healing behavior in the short term is mainly dominated by non-covalent interactions (such as hydrogen bonds). SCP-1 exhibits a faster self-healing speed than SCP-2, which indicates that the hydrogen bonds based on oxime urethane groups in SCP-1 are relatively uniformly distributed, which promotes the self-healing of the material. The above results show that the mechanical properties and self-healing properties can be enhanced simultaneously by controlling the sequence structure of dynamic polymers.

[0109] The present invention provides a sequence control strategy that can simultaneously enhance the mechanical properties and self-healing properties of polymer materials, which is also one of the most pressing challenges in this field. For the first time, the performance of dynamic polymers is regulated by controlling the sequence of dynamic covalent groups. Benefiting from the effect of sequence structure, the mechanical properties and self-healing properties of SCP-1, in which oxime urethane groups are relatively evenly distributed in the molecular chain, are significantly better than those of SCP-2 (oxime urethane groups are relatively concentrated in its molecular chain). At the same time, SCP-1 has a stronger energy dissipation capacity than SCP-2, and their degradation behaviors also show sequence dependence. This strategy is also expected to be applicable to different dynamic covalent systems (such as disulfide bonds, imine bonds, urea bonds). Therefore, this work proposes a new general strategy for the design of high-performance dynamic polymers.

Claims

1. A polyoxime urethane, characterized in that: The structural formula of the polyoxime urethane is: wherein m=an integer of 1 to 30; n=an integer of 1 to 30; x=an integer of 1 to 30; and R is a part of diisocyanate without two isocyanate groups.

2. A method for preparing polyoxime urethane, comprising method 1 or method 2, Method 1: Mix diol, oxime, diisocyanate and solvent, and stir and dissolve them under protective gas at room temperature. Adding a catalyst, stirring, then heating, and drying to obtain polyoxime urethane; The method 2 comprises mixing a diol, a diisocyanate and a solvent, stirring and dissolving them under protective gas conditions at room temperature, adding a catalyst, stirring, and then adding an oxime and a diisocyanate, stirring, heating, and drying to obtain a polyoxime urethane.

3. The preparation method according to claim 2, characterized in that: In the method 1 and the method 2, the diol is polytetramethylene glycol; wherein the molecular weight of the diol is 500-5000 g mol -1 ; The oxime is dimethylglyoxime; the diisocyanate is isophorone diisocyanate; the solvent is anhydrous tetrahydrofuran; the catalyst is dibutyltin dilaurate; The protective gas is nitrogen.

4. The preparation method according to claim 2, characterized in that: In the method 1 and the method 2, the molar ratio of diol, oxime and diisocyanate is 1-3:2-4:4-6, the amount of catalyst is 0.001-1% of the total mass of the reactants, and the amount of solvent is 0.1-50 times the total mass of the diol.

5. The preparation method according to claim 2, characterized in that: In the method 1, the diol, oxime, diisocyanate and solvent are mixed in the following steps: the diol, oxime, diisocyanate and solvent are added in sequence and mixed; In the method 2, the diol, diisocyanate and solvent are mixed in the following steps: the diol, diisocyanate and solvent are added in sequence and mixed.

6. The preparation method according to claim 2, characterized in that: In method 1, diol, oxime, diisocyanate and solvent are mixed, stirred and dissolved under protective gas conditions at room temperature, a catalyst is added, and the temperature is raised to 60° C. and stirred for 1-3 hours, then gradually raised to 90° C. within 12 hours, and dried to obtain polyoxime urethane.

7. The preparation method according to claim 2, characterized in that: In method 2, the diol, the first part of the diisocyanate, and the solvent are mixed, stirred and dissolved under protective gas conditions at room temperature, a catalyst is added, and stirred at 60° C. for 0.5-2 h, and then oxime and the remaining diisocyanate are added, stirred for 1-2 h, and then gradually heated to 90° C. within 12 h, and dried to obtain polyoxime urethane.

8. The preparation method according to claim 7, characterized in that: The first portion of diisocyanate accounts for 1 / 4 to 1 / 2 of the total amount of diisocyanate.

9. Use of the polyoxime urethane according to claim 1 in tire and shoemaking industries.